A model for evidence-based electrotherapy in an undergraduate curriculum - M. Papadopoulos; R. Jordaan (AOSIS, 2000)
All physiotherapists have a responsibility not only to their patients but also to their colleagues and health care funding sources to provide interventions that are sound in theory and supported by well-controlled experimental studies. The principles of evidence-based practice should be implemented in an undergraduate curriculum in order to assist students to acquire skills to obtain and use relevant information. The aim of this paper is to present a model to integrate the activities of patient assessment and information processing, critical appraisal and evidence-based practice into clinical decision making of electrotherapy application. The model as well as the results and evaluation thereof are discussed.